Sequence Characterization and Spatiotemporal Expression Patterns of PbS26-RNase Gene in Chinese White Pear (Pyrus bretschneideri) - Lin Zhang; Baoguang Jia; Feng Zou; Xiaofeng Tan; Min Liu; Zhibo Song; Yanling Zeng; Nan Jiang; Deyi Yuan (The Scientific World Journal)
Many flowering plants exhibit an important intraspecific reproductive barrier phenomenon, that is, self-incompatibility (SI), in which S-RNase genes play a significant role. To clarify the specific function of S-RNase genes in Chinese pears, the full length cDNA of PbS26-RNase was isolated by rapid amplification of cDNA ends (RACE) technology from Chinese white pear (Pyrus bretschneideri) cultivar “Hongpisu.” The cDNA sequence for PbS26-RNase was deposited in GenBank under accession number EU081888. At the amino acid level, the PbS26-RNase displayed the highest similarity (96.9%) with PcSa-RNase of P. communis, and only seven amino acid differences were present in the two S-RNases. Phylogenetic analysis of rosaceous S-RNases indicated that the PbS26-RNase clustered with maloideous S-RNases, forming a subfamily-specific not a species-specific group. The PbS26-RNase gene was specifically expressed in the style but not other tissues/organs. The expression level of the PbS26-RNase gene rapidly increased at bell balloon stage (BBS), and then it dropped after pollination. However, the abundance of the PbS26-RNase gene transcript in the style was greater after cross-pollination than after self-pollination. In addition, a method for rapidly detecting the PbS26-RNase gene was developed via allele-specific primers design. The present study could provide a scientific basis for fully clarifying the mechanism of pear SI at the molecular level.